Epidemiological intricacies of respiratory pathogens: a single-center study on infection dynamics in Beijing, 2023–2024 - Wang Jie; Huo Wenyan; Liu Chang; Feng Jinghong; Li Wenyi; Li Shanshan; Su Ming (Frontiers in Public Health, 2025)
BackgroundFollowing China’s post-COVID-19 reopening strategy, intermittent small-scale outbreaks of respiratory pathogen infections have been observed in the Beijing region. This single-center study aims to characterize the epidemiological features and co-detection patterns of respiratory pathogens in Beijing, providing a scientific basis for the prevention and control of respiratory infectious diseases.MethodsWe performed a retrospective analysis of 19,535 patients undergoing SARS-CoV-2 testing and 12,372 patients screened for six respiratory pathogens, including Mycoplasma pneumoniae (MP), respiratory syncytial virus (RSV), human rhinovirus (HRV), influenza A virus (IAV), adenovirus (ADV), and influenza B virus (IBV) at Peking University People’s Hospital from January 2023 to December 2024. Epidemiological data were systematically collected and analyzed.ResultsSARS-CoV-2 positivity rate maintained above 3% throughout the observation period. IAV demonstrated distinct seasonal peaks in March 2023 (41.9%, 52/124), November–December 2023 (24.5%, 119/485 to 21.9%, 208/950), and December 2024 (25.4%, 289/1136). Poly-epidemics of multiple pathogens emerged between October 2023 and April 2024. Pediatric populations showed highest prevalence of MP (21.4%, 158/740), co-detection (15%, 111/740) and ADV (12.7%, 94/740), while adults predominantly exhibited SARS-CoV-2 (35.1%, 674/1920), RSV (15.8%, 304/1920) and IAV (12.3%, 236/1920). Among 324 co-detection cases, MP (130 cases), HRV (117 cases), and IAV (111 cases) were most frequently involved, with MP + HRV (36 cases), MP + IAV (31 cases), and HRV + IAV (23 cases) being the predominant pairwise combinations.ConclusionBeijing experienced alternating waves of respiratory pathogen epidemics and co-detections during 2023–2024. IAV maintained characteristic winter–spring seasonality, while MP emerged as the predominant pathogen in co-detection events. Distinct pathogen profiles between pediatric and adult populations underscore the necessity for continuous surveillance and age-specific prevention strategies for respiratory infections.